How Did Channel Systems Survive High Sea Level Periods? New Sedimentological Insights from Outcrop, Modern Analogue and Subsurface Data in the Lower Kutai Basin, E. Kalimantan - Erlangga Septama; Pambudi Suseno; Chandra Mustopa EP; Gilang Nuansa; Febri Iswanto; Rizky Andi (Ikatan Ahli Geologi Indonesia, 2019)
It is generally assumed that fluvial depositions reached their peak in low sea level conditions and that high sea levels were generally considered as a period of neglected breaks in sedimentation and thus were ordinarily interpreted to be associated with an abandonment phase. In contrast, our recent findings from outcrop and subsurface data in the Lower Kutai Basin, East Kalimantan has revealed a complex response in the channel-fill development stages within relatively high sea level periods (either authigenic or allogenic factors). Evidence has shown that some channels certainly “survived” the abandonment period.A three km detailed transect was measured through several road cuts and coal mines in the Samarinda Anticlinorium area. The well log, FMI, pressure analysis and core petrographic analyses permit an assessment of the subsurface pattern. The integrated biostratigraphy data (foraminifera, nanno-plankton and palynology) are used to synthesize the regional marker. This study also benefitted from unmanned aerial vehicle (UAV) mapping, which created a high resolution (1-3 cm precision) 3D digital outcrop model (DOM). To complete the final perspective view, the recent channel deposits in the Mahakam Delta and Balikpapan bay are also used as a comparative model. These entire measurements and intensive amount of information are synthesized into the integrated geological model.We identify three typical depositional models of highstand channels due to their specific responses at the channel upper boundary, namely: i) drowned fluvial channel, ii) backfilled/keep-up channel and iii) fluvial channel to shoreface rejuvenation. This study also reveals new insights about the sedimentary processes and facies geometries in the Lower Kutai basin. This unique phenomenon was affected by (a) a large tidal prism area that covers the entire delta systems and (b) a short (40-45 km.) fluvial to shelf sedimentation conduits, combined with (c) relatively high sedimentation fluxes. This type of sand has been long overlooked and currently become recognized as a new bypassed oil reservoir. This new insight is noteworthy toward the re-assessment of the geological model.